1996
DOI: 10.1145/248157.248168
|View full text |Cite
|
Sign up to set email alerts
|

Receiver-driven layered multicast

Abstract: State of the art, real-time, rate-adaptive, multimedia applications adjust their transmission rate to match the available network capacity. Unfortunately, this source-based rate-adaptation performs poorly in a heterogeneous multicast environment because there is no single target rate -the conflicting bandwidth requirements of all receivers cannot be simultaneously satisfied with one transmission rate. If the burden of rate-adaption is moved from the source to the receivers, heterogeneity is accommodated. One a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
269
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(272 citation statements)
references
References 29 publications
1
269
0
2
Order By: Relevance
“…For example, recent research has shown the possibility of incorporating congestion avoidance mechanisms such as Receiverdriven Layered Multicast (RLM) within UDP-based streaming applications such as packet video [McCanne96;Bolot94]. Further research and development on ways to accomplish congestion avoidance for streaming applications will be very important.…”
Section: Non-responsive Flowsmentioning
confidence: 99%
“…For example, recent research has shown the possibility of incorporating congestion avoidance mechanisms such as Receiverdriven Layered Multicast (RLM) within UDP-based streaming applications such as packet video [McCanne96;Bolot94]. Further research and development on ways to accomplish congestion avoidance for streaming applications will be very important.…”
Section: Non-responsive Flowsmentioning
confidence: 99%
“…In order to provide television-like services, efficient multimedia coding on reliable multicast networks has been an area of active research [11][12][13]. With wireless networks fast becoming ubiquitous, an imperative direction is to tailor future applications and protocols to adapt accordingly.…”
Section: Related Workmentioning
confidence: 99%
“…Hellge et al proposes to increase the robustness of more important layers by generating protection across layers. This approach is similar to receiver driven layered multicast (RDLM) [7]. Additionally, authors describe an extension of the Raptor FEC code which allows the implementation of a Layered FEC solution.…”
Section: Media Aware Fecmentioning
confidence: 99%